DIVERSITY OF GENUS ARTOCARPUS ON THE RIVER BARS OF TANTA VILLAGE, TABALONG DISTRICT AS AN ENRICHMENT OF KINGDOM PLANTAE SUBCONCEPT MATERIAL IN SMA IN BOOKLET - Syifa, Noor; Irianti, Riya; Mahrudin, Mahrudin (Universitas PGRI Sumatera Barat, 2024)
Utilizing the local potential of part of the Artocarpus group, can be used as contextual teaching material in education by utilizing teaching materials in the form of brochures. Utilizing local potential-based learning with this brochure can improve student learning outcomes. The aim of this study is to explain the variation of Artocarpus (Artocarpus group) in Tanta Village, Tabalong Regency. Describe the validity and test the practicality of a brochure regarding Artocarpus variations (Artocarpus type) in Tanta Village, Tabalong Regency which was created as a source of learning material for the kingdom plantae sub-concept in high school. The approach used in this study is research & development using the Plomp model up to 5 phases, with restrictions on the implementation phase to distribution in experimental schools and the internet or website. Research findings identified 6 types and 3 varieties of Artocarpus, namely, Artocarpus heterophllyus (Jackfruit, Jackfruit Billulang, Jackfruit Porridge), Artocarpus atilitis (Breadfruit), Artocarpus elasticus (Terap), as well as Artocarpus integer (Cempedak), Artocarpus teysmanni (Water Cempedak), Artocarpus lanceifolius (keledang). The findings for making brochures based on the validity evaluation are said to be very strong with an average value of 3.7, the usability evaluation is classified as very effective with an average value of 91.15%. When a work is considered very valid and very effective, it can be used as an addition to the Biology learning process, especially on the topic of kingdom plantae in high school.